1972
DOI: 10.1136/gut.13.2.138
|View full text |Cite
|
Sign up to set email alerts
|

A clinical evaluation of ano-rectal pressure studies in the diagnosis of Hirschsprung's disease

Abstract: SUMMARY Stimulation of the rectum by stretch results, in the normally innervated bowel, in the reflex relaxation of the internal anal sphincter. The absence of this rectosphincteric reflex in Hirschsprung's disease forms the basis of a simple and safe diagnostic test. Our experience over two years using a simplified air-filled pressure probe system is described, based on the examination of 267 infants and children with abnormal bowel function, of whom 114 were suffering from Hirschsprung's disease.A review of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
1
1

Year Published

1973
1973
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(28 citation statements)
references
References 15 publications
0
26
1
1
Order By: Relevance
“…False-negative test results were found in 4 infants, 3 of whom were <1 month old. In a study by Aaronson and Nixon,19 26% of the patients with a final diagnosis of HD showed a normal RAIR. The authors attributed these false-negative results to displacement of the transducer probe with side-hole sensors.…”
Section: Discussionmentioning
confidence: 95%
“…False-negative test results were found in 4 infants, 3 of whom were <1 month old. In a study by Aaronson and Nixon,19 26% of the patients with a final diagnosis of HD showed a normal RAIR. The authors attributed these false-negative results to displacement of the transducer probe with side-hole sensors.…”
Section: Discussionmentioning
confidence: 95%
“…Both methods were used in our study. A similar technique was used by Howard & Nixon (1968) (9) andAaronson & Nixon (1972) (1).…”
mentioning
confidence: 95%
“…Aganglionosis leads to loss of internal anal sphincter relaxation when the rectum is distended [54,55]. Aganglionosis leads to loss of internal anal sphincter relaxation when the rectum is distended [54,55].…”
Section: Hirschsprung's Diseasementioning
confidence: 99%